Peroxidase and phenylalanine ammonia-lyase activities, phenolic acid contents, and allelochemicals-inhibited root growth of soybean - Herrig, V; De Lourdes, M.; Ferrarese, MDL; Suzuki, L. S.; Rodrigues, J. D.; Ferrarese, O. (Sociedad Biolgia Chile, 2002)
The influence of the allelochemicals ferulic (FA) and vanillic (VA) acids on peroxidase (POD, EC 1.11.1.7) and phenylalanine ammonia-lyase (PAL, EC 4.3.1.5) activities and their relationships with phenolic acid (PhAs) contents and root growth of soybean (Glycine max (L.) Merr.) were examined. Three-day-old seedlings were cultivated in nutrient solution containing FA or VA (0.1 to 1 mM) for 48 h. Both compounds (at 0.5 and 1 mM) decreased root length (RL), fresh weight (FW) and dry weight (DW) and increased PhAs contents. At 0.5 and 1 mM, FA increased soluble POD activity (18% and 47%, respectively) and cell wall (CW)-bound POD activity (61% and 34%), while VA increased soluble POD activity (33% and 17%) but did not affect CW-bound POD activity. At I mM, FA increased (82%) while VA reduced (32%) PAL activities. The results are discussed on the basis of the role of these compounds on phenylpropanoid metabolism and root growth and suggest that the effects caused on POD and PAL activities are some of the many mechanisms by which allelochemicals influence plant growth.
Keywords: roots; phenolic acids; phenylalanine ammonia-lyase; peroxidase; soybean